Digital Classics Outside the Echo-Chamber Teaching, Knowledge Exchange & Public Engagement - Romanello, Matteo; Bodard, Gabriel (Ubiquity Press, 2016)
This volume, edited by the organizers of the "Digital Classicist" seminars series, presents research in classical studies, digital classics and digital humanities, bringing together scholarship that addresses the impact of the study of classical antiquity through computational methods on audiences such as scientists, heritage professionals, students and the general public. Within this context, chapters tackle particular aspects, from epigraphy, papyrology and manuscripts, via Greek language, linguistics and literature, to imaging and modelling of artefacts, architecture, and technologies and methods in digital classics research. The book is aimed for scholars in the various fields of history, classical studies, digital humanities and archaeology. It will also be of interest to researchers in library and information sciences, informatics and pedagogy.
Description based on print version record.
Knowledge Unlatched Round 2
Keywords: History; History; Electronic books